1998
DOI: 10.1046/j.1365-2273.1998.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of exostoses in the external auditory meatus of surfers

Abstract: Fifty-four surfers and 38 surf life savers were examined and questioned in order to determine the prevalence of exostoses. Seventy-three per cent had evidence of body exostoses in the external auditory meatus. Forty per cent had their ear canals narrowed by 50% or more. The relationship between the number of years spent surfing or life saving and the extent of canal stenosis was highly significant (P < 0.00001). Left and right ears were affected equally in this series and the obstruction appears to begin after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
82
4
4

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(105 citation statements)
references
References 11 publications
14
82
4
4
Order By: Relevance
“…Altas freqüências dessa anomalia foram registradas em pessoas envolvidas em atividades aquáticas intensas (Kroon et al, 2002), como surfistas, mergulhadores e pessoas responsáveis pela obtenção de recursos aquáticos (Standen et al, 1997). Apesar de causas genéticas já terem sido consideradas como determinantes da exostose auditiva, atualmente considera-se que sua etiologia esteja associada a fatores ambientais, especialmente ao contato dos canais auditivos com água fria (Van Gilse, 1983;Kennedy, 1986;Deleyiannis et al, 1996;Standen et al, 1997;Chaplin & Stuart, 1998;Velasco-Vazquez et al, 2000).…”
Section: Patologia óSseaunclassified
“…Altas freqüências dessa anomalia foram registradas em pessoas envolvidas em atividades aquáticas intensas (Kroon et al, 2002), como surfistas, mergulhadores e pessoas responsáveis pela obtenção de recursos aquáticos (Standen et al, 1997). Apesar de causas genéticas já terem sido consideradas como determinantes da exostose auditiva, atualmente considera-se que sua etiologia esteja associada a fatores ambientais, especialmente ao contato dos canais auditivos com água fria (Van Gilse, 1983;Kennedy, 1986;Deleyiannis et al, 1996;Standen et al, 1997;Chaplin & Stuart, 1998;Velasco-Vazquez et al, 2000).…”
Section: Patologia óSseaunclassified
“…2 Exostoses are bony growths of the external auditory canal which develop in response to cold water exposure. 3 Such exostoses are usually asymptomatic. However, if large they can cause conductive hearing loss, recurrent otitis externa and otalgia.…”
Section: Introductionmentioning
confidence: 98%
“…Epidemiological studies of surfing communities in several countries have identified a higher prevalence of exostoses in populations exposed to colder waters. [3][4][5][6] This has led to many experts advocating the use of ear plugs or wetsuit hoods to prevent the ingress of cold water into the external auditory canal. Such precautionary measures should prevent the development and limit the progression of exostoses.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is indicated where conservative measures are inadequate. Epidemiological studies of surfing communities in New Zealand [1], Australia [3], Japan [4] and the United States [5] have identified a higher prevalence of exostoses in populations exposed to colder waters. Earplug use prevents the ingress of cold water to the external auditory canal, and so they are believed to prevent or limit the progression of exostoses.…”
Section: Introductionmentioning
confidence: 99%
“…External auditory canal exostoses, more commonly referred to as ''surfer's ear'', are bony growths that develop in response to cold water exposure [1]. Exostoses are usually asymptomatic but, if they are large, can cause conductive hearing loss, recurrent otitis externa and otalgia [2].…”
Section: Introductionmentioning
confidence: 99%